Hearing silenced voices: a learning-centred approach to sustainable land rehabilitation and natural resource management - Wolff, Margaret Gascoyne (Rhodes University, Faculty of Education, Department of Education, 2019)
South Africa is a semi-arid country with dysfunctional water management. The National Water Act encourages integrated water resource management and public participation in contributing to strategies for managing water within delineated areas. Various challenges hamper progress of integrated water resource management and meaningful participation by residents in catchments across the country. One of the challenges is the lack of knowledge about their role in water resource management. By viewing catchments as complex social-ecological systems, this case study investigates how to establish a learning-centred approach to catchment management forum (CMF) formation. The study addressed three sub-questions: What activity systems need to be prioritised for community participation in CMF formation? What existing learning can be identified within the activity systems? What are the sources for expansive social learning in and between the activity systems? The study draws on social learning theory, and on cultural historical activity theory as it offers a methodological approach to identifying a learning-centred approach to learning in a catchment context. Drawing on this theoretical framework, for research question 1, I identified five activity systems that are present in the study area, are partly representative of the people who live in the area, and are linked to land and water governance either through their positions as government employees within the sector, or the NLEIP in ways that influence communities' lives and livelihoods. To address question 2, I ran learning-centred workshops and interviewed people who lived in the study area. Careful, respectful listening and participants' use of home language created the safe space in which residents revealed that they know which water resources are important to protect and where breakdowns in communication happen. For question 3, I analysed the data from the workshops and interviews using a cultural historical activity theory framework to identify discursive manifestations of contradictions within and between activity systems which illuminate the potential for expansive social learning. This study recommends developing an understanding of the complex social-ecological context and prioritising co-learning and community participation in a learning-centred approach to catchment management forum formation. For this, there is need to develop in-depth insight into activity systems associated with water governance in local contexts. In this study I identified five of these activity systems, but the study points to a further range of activity systems that need to be considered for a learning-centred approach to be fully established. The study also found that communities are learning via engaging in the rehabilitation work, through engagements in workshops and within the municipal structures. Additionally, the study identified a number of contradictions that can provide sources of learning for taking an expansive learning approach further in CMF formation. Such an approach may provide the space to build bridges of trust between diverse knowledge systems, and has the potential to encourage sustainable co-operation in natural resource management.
Keywords: Watershed management -- South Africa -- Citizen participation; Water-supply -- Management -- Citizen participation; Environmental education -- South Africa